Syntheses, structures and photocatalytic degradation of organic dyes for two isostructural copper coordination polymers involving in situ hydroxylation reaction. Issue 9 (3rd May 2018) - Peng, Yan-Fen; Qian, Lin-Lu; Ding, Jian-Gang; Zheng, Tian-Rui; Zhang, Ya-Qian; Li, Bao-Long; Li, Hai-Yan
Abstract: Two copper(II) coordination polymers, [Cu2 (btre)(hsuc)Cl(H2 O)]·1.5H2 On (1 ) and [Cu2 (btre)(hsuc)Br(H2 O)]·1.5H2 On (2 ) (btre = 1, 2-bis(1, 2, 4-triazol-4-yl)ethane, H3 hsuc = 2-hydroxysuccinic acid), were synthesized by the hydrothermal method via in situ hydroxylation reaction with fumarate (fum), btre and CuCl2 /CuBr2, and characterized by elemental analyses, IR, TG and X-ray diffraction.1 and2 are isostructural and show a 4-connected 2-D network based on [Cu2 O] dimers.1 and2 show good photocatalytic activity for the degradation of organic dyes methylene blue and methyl orange under UV light irradiation. Abstract :